A Comparative Study of Health, Quality of Life and Social Well-Being in Slums of Kanpur City - Singh, Rohit; Kumra, V. K. (National Geographical Journal of India, 2022)
The impact of continuously increasing urban population has resulted acute shortage of housing, opportunity of job and basic amenities, which in turn results in undernourishment, inadequate civic amenities and mushrooming expansion of slums and squatter settlements. Around the world, approximately one billion people live in urban slums, which are typically overcrowded, polluted and lack in basic amenities. The condition of slums is worst in most of the developing countries and India is not an exception. The slums of Kanpur city portray the wretched picture of life in slums. Environmental concern of slums, social problems, disparities, well-being and quality of life are the new realms of geographic study in this post-modern era. The studies concerned with the quality of life are becoming more relevant for inclusive development of society and country as a whole. In Kanpur city 26 per cent population live in 412 slums. The study is based on primary survey of 150 households of 5 selected slums of Kanpur city. In the present study an attempt has been made to determine the quality of life in slums of Kanpur city. For determining the Quality of Life in slums Composite Index and Standard Deviation have been calculated. To calculate the composite index 13 variables are chosen to determine QOL. This paper also attempts to highlight the poverty alleviation programme and policies for slum dwellers of Kanpur City and suggest remedial measures for inclusive development and planning to improve the quality of life in slums